Adherence to Mediterranean diet and patient perception of rheumatoid arthritis. (August 2020) - Ingegnoli, Francesca; Schioppo, Tommaso; Scotti, Isabella; Ubiali, Tania; De Lucia, Orazio; Murgo, Antonella; Marano, Giuseppe; Boracchi, Patrizia; Caporali, Roberto
Highlights: Non-pharmacological intervention to improve disease perception may be of help in the management of Rheumatoid Arthritis (RA). There are no studies evaluating the effects of Mediterranean diet on disease impact using RA Impact of Disease (RAID) score. Higher adherence to Mediterranean diet is associated with a better perception of RA burden using RAID score. Abstract: Objective: To evaluate the association between the adherence to Mediterranean diet (MD) and disease impact, activity, and comorbidities in patients with rheumatoid arthritis (RA). Design: Consecutive patients with RA were enrolled in this cross-sectional study. For each patient, Disease Activity Score on 28 joints (DAS28), Simple Disease Activity Index (SDAI), RA Impact of Disease (RAID), Health Assessment Questionnaire (HAQ), patient global assessment (PGA) and general health (GH) and a self-reported questionnaire called MD score were recorded. Results: 205 RA patients (median age 53 years, female 80.49 %) were enrolled. An association between MD score and HAQ (p-value = 0.033), PGA and GH (p-value 0.023 both) was observed. RAID total score had a statistically significant negative relationship with MD score (p-value = 0.016). A statistically significant negative association was found for pain (p-value = 0.025), functional disability (p-value<0.001), sleep (p-value = 0.041), physical well-being (p-value = 0.027) and coping (p-value = 0.008). Multiple regression analysis to evaluate the relationship between significant RAID items and MD score did not show any statistical significance as all items are strongly related to each other. A negative trend, although not statistically significant was found for DAS28 and SDAI. The only comorbidity associated with MD score was arterial hypertension (OR = 0.94). Conclusions: In this Italian RA cohort, the adherence to MD was significantly associated with a better RAID, PGA and GH, but higher MD score was not significantly associated with lower disease activity. Our study suggests an overall potential beneficial effect of MD in RA patients.